SAPHO Syndrome Presenting With Atlo-Epistrophic Synovitis and Left Vocal Cord Paresis: A Challenging Diagnosis. Issue 15 (September 2022) - Maranini, Beatrice; Ciancio, Giovanni; Rinaldi, Rosa; Borrelli, Massimo; Pugliatti, Maura; Govoni, Marcello
SAPHO (synovitis, acne, pustulosis, hyperostosis, and osteitis) is a rare syndrome mainly characterized by cutaneous and osteoarticular manifestations. The most typical osteoarticular manifestations are localized to the anterior chest wall and include a usually noninfectious osteitis, hyperostosis, and synovitis of the sternoclavicular joints. However, clinical presentation of SAPHO syndrome can be quite heterogeneous. Several clinical and radiological features are shared with other well-defined pathological entities, and clinical signs and symptoms often occur at different timepoints. Mainly due to this complexity and its rarity, there are currently no validated diagnostic criteria for SAPHO syndrome. Inflammation of the soft tissues around the bones and possible nerve compression could contribute to dysphagia, hypophonia, or obstruction of the airways. Neurologic manifestations could therefore be part of this multiorgan involvement. Here, we present a case of SAPHO syndrome with atypical onset symptoms, characterized by left vocal cord paralysis, acute neck pain due to osteolytic atlantoepistrophic lesion, and an unusual cutaneous manifestation, diagnosed as mid-dermal elastolysis. The latest two, to the best of our knowledge, have been here first described in a case of SAPHO syndrome.